Development of the Melanoma Concerns Questionnaire (MCQ‐28); refinement of the EORTC QLQ‐MEL38 module. Issue 2 (4th December 2019) - Winstanley, Julie; White, Edward; Saw, Robyn; Young, Teresa; Burmeister, Bryan; Nikolic, Dejan; Busto‐Cornide, Iria; Iglesias‐Pena, Nicolás; Boyle, Frances
Abstract: Objective: Few patient‐reported outcome measures (PROMs) have been developed that adequately measure the patient‐experience following diagnosis and treatment of melanoma. Building on previous research, which developed the European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Module (QLQ‐MEL38), the aim of this study was to further test the hypothesised domain structure and psychometric properties of the phase 3 module, in a new larger sample of melanoma patients. Methods: Melanoma patients (n = 270) were recruited from four countries (Australia, England, Serbia, and Spain). Patients completed the EORTC core questionnaire (QLQ‐C30), the QLQ‐MEL38, and a sociodemographic survey. Using this new larger dataset, comparisons were made with the hypothesised domain structure of the EORTC phase 3 module using principal component analysis. Items which formed subscales in a revised domain structure were then tested for goodness of fit (GoF) to the Rasch model. Results: The original hypothesised and final domain structures were similar but not identical. Twenty‐four items (83%) loaded onto the same distinct subscales previously generated by phase 3, and item‐by‐item comparison of the two pattern matrices indicated an extremely close match. Ten items were removed from the QLQ‐MEL38 phase 3 module, and rescoring of some items was required. Four subscales, together with five individual items, comprised the final instrument. Conclusion: The newly developed measure (named the Melanoma Concerns Questionnaire; MCQ‐28) was found to tap into several important psychosocial domains of concern to melanoma patients, particularly those being managed in "usual" clinic settings.